Smart Dustbin / Muhammad Aiman Saipullah - Saipullah, Muhammad Aiman; Anuar, Nor Izzat Shazwan; Madzlan, Muhammad Muttaqin; Azlee, Nurlaila Aseelah; Mohd Azman, Hanies Ardeenie (2022)
This New Development Product report intends to inform the prospect consumer and user about the product that will be created. The first process of developing the new product is to identify all the consequences and problems that might happen during the development process and the user will be faced. A survey has been completed that involved almost 33 respondents most of them come from the students of UiTM Arau, Perlis, and a few public respondents. The survey will identify all the problems that might the respondents faced regarding the development of the product that will satisfy the user's need and the market requirement. Moreover, the survey also allows the users to suggest ideas of improvement and the users' opinions about the product. The product is related to the development of a smart dustbin with some technology. The purpose of developing the product is to ease the process of managing the wastes from the dustbin. By providing the technology, it might reduce the user from touching the dustbin which prevents them from having a disease when handling the waste from the product. Based on this survey, the users will be asking about their awareness regarding the handling of waste such as the waste disposal frequency in the household, understanding about the concept of the greenhouse, the type of waste they dispose of, and issues and problems faced by them. They are various issues faced by the respondents when handling the waste disposal process. First, the problem is about the current dustbin was unable to separate the leftover and recycle trash. Currently, the respondents need to manually choose the trash that can be recycled such as plastic, paper, and aluminum. Next, the user needs to manually fold the trash when the dustbin was full and needs to replace the new plastic on the dustbin and it will be time-consuming faced by the respondent to finish the process. Furthermore, the respondents also need to manually lift the dustbin caps to insert the trash. This might give some discomfort for them because their hand will be dirty if there is some leftover was left on the dustbin caps. Due to all the problems mentioned above, a smart dustbin is a proposed idea for the New Development Product. This smart dustbin will provide some current technology that helps the users to reduce their time to manage the leftover and recycle trash. This will be included technology such as a sensor on the dustbin that helps it to separate the wastes. Smart dustbin also will provide the space for the trash according to the type of waste which are leftover and recycle items.